Root Maturation of an Immature Dens Invaginatus Despite Unsuccessful Revitalization Procedure: A Case Report and Recommendations for Educational Purposes - Julia Ludwig; Marcel Reymus; Alexander Winkler; Sebastian Soliman; Ralf Krug; Gabriel Krastl (MDPI AG, 2023)
Background: The clinical management of teeth with complex dens invaginatus (DI) malformations and apical periodontitis may be challenging due to the lack of routine. The aim of this case report is to describe the endodontic treatment of an immature tooth with DI and to discuss strategies for preclinical training for teeth with such malformations. Case report: A 9-year-old male presented with an immature maxillary incisor with DI (Oehlers Type II) and apical periodontitis which was diagnosed by cone beam computed tomography (CBCT). Revitalization was initially attempted but then abandoned after failure to generate a stable blood clot. Nevertheless, considerable increase in both root length and thickness could be detected after medication with calcium hydroxide followed by root canal filling with MTA as an apical plug. Conclusions: The endodontic management of teeth with DI requires thorough treatment planning. In immature teeth, under certain conditions, root maturation may occur even with conventional apexification procedures. From an educational perspective, different strategies including CBCT and 3D-printed transparent tooth models for visualization of the complex internal morphology and redesigned 3D-printed replica with various degrees of difficulty for endodontic training, can be used to overcome the challenges associated with endodontic treatment of such teeth.